Glutathione and glutathione S-transferase levels in patients with liver metastases of colorectal cancer and other hepatic disorders - Baltruskeviciene, Edita; Kazbariene, Birutė; Badaras, Robertas; Bagdonaitė, Loreta; Krikštaponienė, Aurelija; Zdanavičius, Linas; Aleknavicius, Eduardas; Didziapetrienė, Janina (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Glutathione and glutathione S-transferases (GST) are involved in cell defence against reactive oxygen species, which induces oxidative stress and are associated with different chronic diseases. The aim of the present study was to determine the differences in reduced glutathione (GSH) and GST levels in patients with different liver diseases. Materials and Methods: Overall, 114 patients were enrolled in this study: 58 patients with colorectal cancer (18 without and 40 with liver metastases), 27 with liver steatosis, 29 with alcoholic cirrhosis and a group of 40 healthy volunteers. The levels of GSH and GST in blood serum were evaluated by enzyme-linked immunosorbent assay (ELISA) according to the manufacturer’s guidelines. Results: Significant differences in GSH and GST levels were observed in most of the groups compared to the healthy volunteers (GSH: 52.72 µg/mL, GST: 0.53 ng/mL): with hepatic steatosis (GSH: 17.04 µg/mL, p<0.001; GST: 5.89 ng/mL, p<0.001), alcoholic cirrhosis (GSH: 62.04 µg/mL, p<0.003; GST: 0.94 ng/mL, p<0.001) and liver metastases (GSH: 37.84 µg/mL, p<0.001, GST: 1.25 ng/mL, p=0.747). Conclusion: The different GSH and GST levels in patients with colorectal cancer liver metastases, liver steatosis and alcoholic cirrhosis indicate the differences in antioxidative system damage and its compensatory possibilities and could serve as potential biomarkers for its correction.